A three-electrode dual-power-supply electrochemical pumping system for fast and energy efficient lithium extraction and recovery from solutions - Kazuya Sasaki; Kiyoto Shin-mura; Shunsuke Honda; Hirofumi Tazoe; Eiki Niwa (Communications Engineering, 2024)
Abstract The demand for Li-ion batteries (LIBs) for use in electric vehicles, which is key to realizing a decarbonized society, is accelerating. However, the supply of Li resources has recently become a major issue, thereby necessitating the development of economical and sustainable technologies of brine/seawater-based Li extraction and recycling Li from spent LIBs. This paper presents an innovative electrochemical pumping technology based on a new cell structure for Li extraction/recovery. This system can provide large electrochemical driving forces while preventing the occurrence of electronic conduction due to electrolyte reduction. This electrochemical pumping system allows extraction/recovery of Li ions from the anode side to the cathode side, rather than the diffusion of other ions, due to the ion-diffusion-bottleneck size of the electrolyte material. Using this system, high-purity Li can be collected with high energy efficiency and at least 464 times faster than that via conventional electrochemical pumping, even with a commercially available Li-ion electrolyte plate.